In-Situ Raman Investigation of Polysulfide Formation in Li-S Cells - Hagen, M.; Schiffels, P.; Hammer, M.; Doerfler, S.; Tuebke, J.; Hoffmann, M. J.; Althues, H.; Kaskel, Stefan (Journal of The Electrochemical Society, 2013)
To obtain information about the Li-S reaction mechanism through spectroscopy, a Raman literature study, polysulfide vibrational mode calculations and experimental in-situ measurements were performed. A special test cell was constructed to examine in-situ Raman spectra in the spectral range from 100 cm-1 to 600 cm-1during charge and discharge in the voltage range of 1.5 V to 3.0 V. In order to assign the in-situ Raman data and to support the interpretation of the observed changes in the overall Raman-spectrum, several reference measurements on well-defined substances were conducted. The reference measurements included pure solvents, electrolytes and polysulfide solutions prepared from stoichiometric mixtures of S8 and Li2S powders. The assignment of the observed Raman-spectra was fürther based on a comparison with purely theoretical data for the vibrational modes of the polysulfide di-anions Sn2- and radical mono-anions Sn- calculated at the B3PW91/6-311G(2df,p) level of density functional theory (DFT). The DFT data for the vibrational spectra, corrected for solvent effects in the framework of the polarizable continuum model (PCM), allowed an identification of several characteristic features in the in-situ Raman spectra. © 2013, The Electrochemical Society, Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-03-20